STATUS TANAH YANG HILANG AKIBAT MELEBARNYA SEMPADAN SUNGAI BEKASI DITINJAU DARI PERATURAN DAERAH KABUPATEN BEKASI TAHUN 2011-2031 : Land Lost Due The Widening Of Bekasi River Borders From The Regional Regulations Of Bekasi District Year 2011-2031 - Desyda Puspita Anggraini; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2024)
The land that the villagers lived on was simply lost due to the loss of land due to natural events. The problems is Regional Regulation Number 12 of 2011 concerning the Regional Spatial Plan of Bekasi Regency for 2011-2031, the efforts of the Regional Government to restore land rights lost due to the widening of the Bekasi river border. This research uses descriptive normative legal research methods, uses secondary data supported by primary data, and is studied qualitatively. The discussion that the status of land lost due to the widening of the Bekasi river border has been lost, the cause of which is the result of a natural phenomenon that makes the soil erode on the river border land. Local authorities can conduct additional research and address this issue in accordance with relevant laws. The study findings show that there are no regulatory provisions governing the status of lost land on riverbanks in Perda No. 12/2011 on the Bekasi District Spatial Plan 2011-2031. This means that efforts to recover lost land on riverbanks must be carried out in accordance with other regulations. The local government can help by developing policies to check and stop this problem from occurring further losses.